Induction chemotherapy followed by intensity-modulated radiotherapy with reduced gross tumor volume delineation for stage T3-4 nasopharyngeal carcinoma - Xue F (OncoTargets and Therapy, 2017)
Fen Xue,1,2 Chaosu Hu,1,2 Xiayun He1,2 1Department of Radiation Oncology, Fudan University Shanghai Cancer Center, 2Department of Oncology, Shanghai Medical College, Fudan University, Shanghai, People’s Republic of China Purpose: A common problem in stage T3–4 nasopharyngeal carcinoma (NPC) is the narrow gap between the primary tumor and neurological structures, which makes dose optimization difficult. Considering that significant tumor shrinkage may occur during induction chemotherapy (IC), this study explored the efficacy of intensity-modulated radiotherapy (IMRT) using reduced gross tumor volume (GTV) in the treatment of T3–4 NPC.Patients and methods: Between January 2009 and April 2014, 103 patients with non-metastatic stage T3–4 NPC were prospectively recruited. They were assigned to accept IC, followed by reduced-volume IMRT and adjuvant chemotherapy. GTV was based on the post-IC volume of intracavity tumors and lymph nodes, and the pre-IC volume of the remaining involved structures.Results: For all treated patients, the 3-year local failure-free survival (LFFS) was 91.9%. After IC, 91 (88.3%) patients achieved local objective response (OR), and their 3-year LFFS rates were significantly better than in patients who failed to achieve local OR (94.1% vs 75.0%, P=0.023). A multivariate analysis demonstrated the prognostic value of tumor response to IC for LFFS. Dosimetric analysis showed good homogeneity, and the dose constraints were stringent. Asymptomatic temporal lobe necrosis in the ipsilateral side of tumor occurred in one patient.Conclusion: IMRT using a reduced GTV delineation delivered satisfactory doses to the target volumes and avoided overdosing of critical neurological structures. Results showed satisfactory survival outcomes with few treatment-related toxicities. Tumor response to IC could facilitate selection of patients with stage T3–4 NPC eligible for treatment with this method. Keywords: nasopharyngeal carcinoma, intensity-modulated radiotherapy, induction chemotherapy, target delineation